Polymicrobial Composition of Oral Microbiota in Ulceronecrotic Gingivostomatitis: Structure of Microbial Associations and the Role of Key Microorganisms - Sergey, Ashrafov Davud; Suad Afrail, Aliyev Mammad (American Journal of Biology and Natural Sciences, 2026)
The aim of this study was to investigate the species composition of the oral mucosal microbiota and to characterize the structure of microbial associations in patients with ulceronecrotic gingivostomatitis. A clinical and microbiological examination was conducted, with samples collected from pathological lesions of the oral mucosa. Microorganisms were identified using standard bacteriological methods, determining their species affiliation and the nature of microbial associations. Results showed that all patients harbored representatives of both resident and transient microbiota, forming complex polymicrobial associations. In 24.3% of cases, associations included aerobic, anaerobic, and fungal microorganisms, while in 75.7% of cases, the complexes consisted of aerobic and anaerobic flora without fungal components. The average number of species in one association was 7–9, confirming the polymicrobial nature of the inflammatory process. Conclusion: Ulceronecrotic gingivostomatitis is characterized by the formation of complex microbial complexes, in which Fusobacterium nucleatum and Treponema vincentii play a leading role, interacting with other representatives of aerobic, anaerobic, and in some cases, fungal flora.